Estimación de la Q de Tobin de la economía ecuatoriana para probar si esta es un determinante importante en la inversión privada del Ecuador en el periodo 2005-2015 - Cárdenas Jara, María Laura (2018)
This research aims to estimate Tobin q for the Ecuadorian economy to determine if it has a positive relation with private investment over the period 2005-2015. The study employs a panel data model incorporating a data base of 21 companies listed in the Quito and Guayaquil Stock Exchange. The results show that a variation of one percentage point in the estimated growth rate of Tobin q results in a 0.25 percentage point increase in the estimated growth rate of private investment by the listed companies. The results also demonstrate that the cost of investment, as measured by the real interest rate, and liquidity, as measured by the price of oil, play a fundamental role in the investment decisions of the Ecuadorian private sector.